Experimental study regarding the evolution of temperature profiles inside wet cooling tower under crosswind conditions - Gao, Ming; Sun, Feng-zhong; Turan, A. (International journal of thermal sciences, 2014)
Based on similarity theory, this research details a thermal-state model experiment, concerning the evolution of the air/water temperature profiles inside a Natural Draft Wet Cooling Tower (NDWCT) under windless and crosswind conditions. Prior studies have shown that the air/water temperature distribution is fairly uniform and stable under windless (stagnant) conditions, but the uniformity is destroyed in the presence of windy conditions, and the air/water temperature of different points displays a large variation subject to the same crosswind velocity. Generally speaking, the highest air/water temperature values inside the whole tower lie on the windward and leeward direction, but the highest air temperature at the tower outlet appears near the leeward side zone, rather than exactly on the leeward side. Based on this research, the air/water temperature profiles regarding measurement of values can be obtained accurately under windless and crosswind conditions, a fact that can help confirm the specific location of vortex on the windward and leeward side. All of above findings can provide an important theoretical foundation concerning further research, specifically for energy-saving aspects NDWCTs. •Thermal-state model experiment is conducted for wet cooling tower in this paper.•Air/water temperature inside tower displays large variation under windy conditions.•The highest air/water temperature values lie on the windward and leeward side.•Highest air temperature of tower outlet doesn't appear exactly on the leeward side.•Air/water temperature of different points can be obtained under windy conditions.